Fresno Chapter of Hastings Alumni Association Luncheon at Downtown Club - Watkins, Howard::::::::: (1984)
Fresno Chapter Alumni members eating lunch; on left: Rick Jensen, Robert Bergstrom; last three on right: Judge Jane York, Darci Reid Noxon, Steven Noxon